Chronic kidney disease: Cystatin C as a diagnostic marker. - Lambis-Loaiza, Laura Alejandra (2022)
Chronic kidney disease is a disease with high levels of morbidity and mortality; Currently, it is diagnosed with serum creatinine and estimating GFR, being the CKD-EPI and MDRD equations the most used. An extensive search of the literature was carried out in different databases to reveal aspects of chronic kidney disease, its conventional diagnosis and new diagnostic methods. Measuring serum creatinine is not sufficient to assess kidney function, while cystatin C, by freely filtering through the kidney and not binding to plasma proteins, makes this the most accurate measure to estimate kidney function. There is still no precise marker to correctly assess the glomerular filtration rate, however, cystatin C is of great diagnostic utility for kidney failure, since its elevated levels identify a greater risk for kidney disease.